Super-viscous anti-slip sealing layer and construction method and application thereof
The super-sticky anti-skid seal layer addresses rapid wear and friction loss on highways by using emulsified asphalt with modifiers and fillers, enhancing durability and water resistance, thus improving safety and reducing maintenance costs.
Patent Information
- Application Number
- CN202411532045.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2024-12-27
AI Technical Summary
Highways with significant traffic volume and large freight vehicles experience rapid wear and loss of friction coefficient, leading to safety hazards and increased maintenance costs, while existing maintenance methods disrupt the pavement structure and are costly.
A super-sticky anti-skid seal layer composed of emulsified asphalt layers with specific modifiers, fillers, and stabilizers, enhancing adhesion, durability, and water resistance, combined with a crushed stone layer for improved structural integrity.
The anti-skid seal layer improves road safety and extends service life by maintaining friction and preventing water damage, reducing maintenance costs, and adapting to various environmental conditions.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of road engineering materials, and in particular relates to a super-adhesive anti-slip sealing layer, and a construction method and application thereof. Background Art
[0002] For highways with large daily traffic volume, especially those with a large proportion of large freight vehicles, it is easy to cause the wheel track of the channelized pavement to wear too quickly, and the friction coefficient of the pavement to drop too quickly, which will cause hidden dangers to driving safety. With the increase of road age, the asphalt surface layer shows a deterioration trend, resulting in loose cracks, which leads to aggravated water damage, and cracks, subsidence, potholes and other diseases on some pavements. According to the changes in the service life of pavements maintained at different times, if no maintenance measures are taken, the pavement condition and service life will be seriously attenuated, resulting in a sharp increase in pavement maintenance costs. Existing maintenance technologies, such as thin-layer overlay, milling and resurfacing, etc., usually require full cross-section construction, which destroys the balance of the original pavement structure and increases maintenance costs. At the same time, the operation process of some mountain highway bridges and tunnels and long slope pavements is restricted by objective conditions, such as heavy rain, short operation time, low controllability, and great interference with vehicle traffic.
[0003] Therefore, in view of the problems of insufficient anti-skid performance and water damage on existing expressways, as well as the objective limitations of construction and geographical environment, it is necessary to develop a road engineering material that is economical and environmentally friendly, efficient in construction, excellent in anti-skid performance, and has a significant water-sealing effect, so as to improve the long-term effectiveness of preventive maintenance technology, extend the service life of the road surface, and meet application scenarios with different needs. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems of insufficient anti-skid performance, water damage and diseases existing in the above-mentioned expressways, as well as the shortcomings related to the objective conditions of construction and geographical environment, and to provide a super-adhesive anti-skid seal. The present invention adopts the following technical solutions: A super-sticky anti-skid seal layer comprises a bottom layer of emulsified asphalt, a crushed stone layer and a surface layer of emulsified asphalt, wherein the bottom layer of emulsified asphalt is made of the following raw materials in parts by weight: 65-75 parts of base asphalt, 3-8 parts of asphalt modifier, 10-15 parts of a first filler, 3-5 parts of a tackifier, 2-5 parts of an emulsifier, 3-5 parts of a stabilizer, 3-5 parts of a cross-linking agent, 30-40 parts of water, and 5-8 parts of an auxiliary agent; and the surface layer of emulsified asphalt is made of the following raw materials in parts by weight: 65-75 parts of base asphalt, 3-8 parts of an asphalt modifier, 15-20 parts of a second filler, 3-5 parts of a tackifier, 2-5 parts of an emulsifier, 3-5 parts of a stabilizer, 3-5 parts of a cross-linking agent, 30-40 parts of water, and 5-8 parts of an auxiliary agent.
[0005] Specifically, the base asphalt is the main component of the emulsified asphalt, providing basic bonding and waterproofing properties for the entire system. Further, the asphalt modifier can significantly improve the high and low temperature performance and elongation at break of the asphalt. Further, the first filler and the second filler can increase the solid content of the emulsified asphalt, improve the thickness and durability of the coating. Further, the tackifier can enhance the bonding force between the emulsified asphalt and the base surface, and improve the adhesion of the coating. Further, the emulsifier can ensure that the asphalt particles are stably dispersed in the water to form a uniform emulsion, which has the effect of reducing the interfacial tension between the asphalt and the water. Further, the stabilizer helps to maintain the stability of the emulsified asphalt, helps to ensure the long-term stability of the emulsion, and prevents the emulsion from stratification or water loss. Further, the cross-linking agent can promote the cross-linking reaction between the asphalt molecules, help to improve the overall performance of the emulsified asphalt, and improve the strength and durability of the coating. Further, water provides the necessary medium for the formation of the emulsion, which can ensure that the emulsion has good fluidity and construction performance.
[0006] The base asphalt is one of No. 70 or No. 90 road petroleum asphalt, and the asphalt modifier includes at least two of styrene-butadiene-styrene block copolymer, styrene-butadiene rubber, and ethylene-vinyl acetate copolymer.
[0007] Specifically, No. 70 or No. 90 road petroleum asphalt has good fluidity, thermal stability, long-lasting adhesion, elastic-plasticity, electrical insulation and water resistance. Specifically, No. 70 road petroleum asphalt has low wax content, good crack resistance, good brittleness resistance, good high temperature stability, strong strain capacity and strong rutting resistance. No. 90 road petroleum asphalt has the characteristics of high ductility, good plasticity and durability, large ratio of evaporation to needle penetration, good product homogeneity and heat aging resistance. In areas with higher temperatures, No. 70 asphalt has better resistance to high temperature deformation and reduces the occurrence of rutting; in areas with lower temperatures, No. 90 asphalt is beneficial to prevent the road surface from cracking at low temperatures.
[0008] Specifically, styrene-butadiene-styrene block copolymers have excellent tensile strength, elasticity and electrical properties, and in asphalt modification, can significantly improve the low-temperature flexibility and high-temperature stability of asphalt.
[0009] Specifically, styrene-butadiene rubber has the advantages of wear resistance, cold resistance, low heat generation, low shrinkage, etc. In asphalt modification, it can enhance the adhesion and durability of asphalt, and improve the crack resistance and rutting resistance of the road surface.
[0010] Specifically, ethylene-vinyl acetate copolymer has good softness, elasticity, and excellent anti-aging and ozone resistance. In asphalt modification, it can improve the flexibility and weather resistance of asphalt, and increase the durability and service life of the road surface.
[0011] Furthermore, the combination of styrene-butadiene-styrene block copolymer and styrene-butadiene rubber can make the emulsified asphalt less likely to flow and deform at high temperatures, maintain good flexibility at low temperatures, and reduce the occurrence of cracks.
[0012] Furthermore, the combination of styrene-butadiene-styrene block and ethylene-vinyl acetate copolymer can make the emulsified asphalt resist erosion by aging factors such as ultraviolet rays and oxidation during long-term use, while maintaining a good load-bearing capacity under vehicle load.
[0013] Furthermore, the combination of styrene-butadiene rubber and ethylene-vinyl acetate copolymer makes the emulsified asphalt perform well in bonding aggregates, while also maintaining good performance under complex environmental conditions. For example, in a humid environment, the good bonding properties can reduce the spalling of aggregates, and its aging resistance can ensure the stability of the road surface under long-term sun and rain.
[0014] Specifically, by combining the base asphalt with at least two asphalt modifiers, it is possible to prepare modified bottom layer super-viscous emulsified asphalt and surface layer super-viscous emulsified asphalt with excellent performance. This asphalt not only has excellent adhesion, waterproofness and durability, but also can maintain stable performance under different temperature conditions. At the same time, due to the use of multiple modifiers for composite modification, the comprehensive performance of asphalt can be further improved to meet the needs of various complex application scenarios.
[0015] The first filler includes at least three of modified silicon dioxide, nano calcium carbonate, polypropylene composite particles, modified montmorillonite, and modified carbon nanotubes.
[0016] Specifically, the modified silica of the present invention is γ-(2,3-epoxypropoxy)propyltrimethoxysilane-modified silica. The modified silica has higher dispersibility and reactivity, and can enhance the mechanical strength and wear resistance of the coating. In emulsified asphalt, the modified silica has a high specific surface area, which can enhance the interfacial bonding force with asphalt, improve the strength and stability of the emulsified asphalt, and reduce the deformation of the road surface during use. Furthermore, the modified silica can be used as a reinforcing agent to increase the hardness and durability of the coating. Improve the high temperature performance of the emulsified asphalt, so that it is not easy to soften and flow at high temperatures.
[0017] The preparation steps of γ-(2,3-epoxypropoxy)propyltrimethoxysilane modified silica are as follows: N1. Dry the nano-silica at 100°C for 2-4 hours to remove the moisture adsorbed on the surface, and cool to room temperature; N2. Prepare a γ-(2,3-epoxypropoxy)propyltrimethoxysilane-ethanol solution with a γ-(2,3-epoxypropoxy)propyltrimethoxysilane concentration of 1%. Use hydrochloric acid to adjust the pH value of the solution to 3-4 to promote the hydrolysis reaction of silane. Add the dried silica to the silane solution to allow the silane to fully contact and coat the surface of the silica. Heat the mixture to 50-60°C and stir with a magnetic stirrer or mechanical stirrer for 2-4 hours to promote the hydrolysis and condensation reaction of silane. N3. Filter the modified silica and wash it with anhydrous ethanol and deionized water several times to remove unreacted silane and other impurities. Dry the washed silica at 60-80°C for 4-6 hours until it is completely dry.
[0018] Specifically, nano calcium carbonate has an excellent reinforcing effect and can significantly improve the strength and toughness of coatings. The nanoscale size of nano calcium carbonate enables it to be evenly dispersed in asphalt to form a dense filling network, which can fill the tiny pores in asphalt, improve the density and waterproof performance of emulsified asphalt, enhance the hardness and wear resistance of emulsified asphalt, and reduce the wear of the road surface.
[0019] Specifically, the polypropylene composite particles are made of glass fiber and polypropylene composite materials, which have excellent heat resistance and weather resistance, and can increase the thermal stability and service life of emulsified asphalt. In emulsified asphalt, the polypropylene composite particles can be used as an anti-aging agent to prevent asphalt from aging due to long-term exposure to sunlight.
[0020] Specifically, the modified montmorillonite is montmorillonite modified with hexadecyltrimethylammonium bromide, which has good water absorption and swelling properties, and can increase the adhesion and impermeability of asphalt. In emulsified asphalt, it can be used as a waterproofing agent to improve the waterproof performance of the coating and improve the rheological properties of emulsified asphalt, making it easier to apply and shape during construction.
[0021] The preparation method of modified montmorillonite is: M1: Sodium montmorillonite is dissolved in deionized water, and an exfoliated montmorillonite suspension is obtained under stirring, and the mass concentration of montmorillonite in the suspension is 0.1-2%; M2: Add hexadecyltrimethylammonium bromide to deionized water, stir evenly to prepare a hexadecyltrimethylammonium bromide solution, and adjust the pH value to 6-8; M3: Slowly add hexadecyltrimethylammonium bromide to the exfoliated montmorillonite suspension. The reaction temperature is controlled at 50-100°C and the reaction time is 90-210 minutes; M4: The reaction product is centrifuged and washed 2-5 times to remove unreacted hexadecyltrimethylammonium bromide and other impurities, and dried at 70-80°C for 12-18 hours to remove moisture and residual solvent.
[0022] Specifically, the modified carbon nanotubes are polyaniline-modified carbon nanotubes, which have excellent mechanical properties and can significantly improve the strength and toughness of emulsified asphalt. They have good electrical conductivity and can promote the self-healing properties of emulsified asphalt. When microcracks appear on the road surface, they can accelerate the flow and healing process of asphalt. At the same time, the modified carbon nanotubes can improve the thermal conductivity of emulsified asphalt, which is beneficial for the heat dissipation of the road surface at high temperatures and reduce the generation of rutting.
[0023] The method for preparing polyaniline-modified carbon nanotubes comprises the following steps: P1. Add aniline monomer into deionized water, stir evenly, prepare an aniline solution of a certain concentration, and adjust the pH value of the aniline solution to 2-3 with hydrochloric acid to promote the protonation of aniline; P2. Disperse 100 mg of multi-walled carbon nanotubes in an appropriate amount of deionized water, use an ultrasonic disperser to disperse for 30 minutes to ensure that the carbon nanotubes are evenly dispersed, and wash the dispersed carbon nanotubes with deionized water several times to remove impurities; P3. Add the dispersed carbon nanotubes to the aniline solution to ensure that the carbon nanotubes are completely immersed in the solution; use a magnetic stirrer or a mechanical stirrer to stir for 30-60 minutes at room temperature to obtain a mixed solution, so that the aniline can fully contact and adsorb on the surface of the carbon nanotubes; dissolve an appropriate amount of ammonium persulfate in a small amount of deionized water, and then slowly add it to the above mixed solution; cool the mixed solution to 0-5°C in an ice bath, and continue stirring for 4-8 hours to promote the in-situ polymerization of polyaniline on the surface of the carbon nanotubes.
[0024] P4. Filter the modified carbon nanotubes and wash them with deionized water and anhydrous ethanol for multiple times to remove unreacted aniline, ammonium sulfate and other impurities. Dry the washed carbon nanotubes at 60-80° C. for 4-6 hours until they are completely dry.
[0025] The above-mentioned at least three fillers are used in combination to prepare a modified super-sticky bottom emulsified asphalt with excellent performance. These fillers can form a multi-layered filling network in the asphalt to enhance the mechanical properties and durability of the coating. At the same time, due to the synergistic effect between different fillers, the present invention can further improve the comprehensive performance of the coating, such as improving the hardness, wear resistance, heat resistance, weather resistance and bonding strength of the coating film.
[0026] The second filler includes at least three of ultra-high molecular weight polyethylene, basalt particles, silicon carbide, glass fiber, and wollastonite.
[0027] Specifically, ultra-high molecular weight polyethylene has extremely high wear resistance. In the surface emulsified asphalt, when the vehicle generates friction during driving, it can serve as a wear-resistant skeleton structure to reduce the wear on the seal layer caused by the friction between the tire and the road surface. High molecular weight polyethylene can increase the flexibility and impact resistance of the surface emulsified asphalt. The surface emulsified asphalt can maintain good performance under different temperature conditions, especially under low temperature conditions, and is not prone to brittle cracking. In order to improve the interface bonding effect between ultra-high molecular weight polyethylene and other materials, specifically, ultra-high molecular weight polyethylene particles are placed in a ball mill, grinding medium steel balls are added, and ball milling is performed for 3-5 hours at a rotation speed of 300-500r / min to reduce the particle size of the ultra-high molecular weight polyethylene particles, thereby increasing its surface activity. When the ultra-high molecular weight polyethylene after ball milling is mixed with materials such as asphalt, it can be better dispersed and form a good interface bonding.
[0028] Specifically, basalt particles are hard and rough. In the surface emulsified asphalt, it can increase the roughness of the seal surface, thereby increasing the friction between the tire and the road surface. Basalt particles themselves have high compressive strength and can play a reinforcing role in the seal structure. When the vehicle load acts on the road surface, it can share part of the pressure, making the overall structure of the seal more stable and reducing the possibility of deformation and damage.
[0029] Specifically, silicon carbide has the characteristics of high hardness and high wear resistance. It can effectively resist the wear of vehicle tires, and at the same time form a rough microstructure on the road surface, further increasing the anti-skid performance of the road surface. Silicon carbide can improve the effect of the seal layer against rain, chemical pollutants, and ultraviolet radiation, which helps to maintain the long-term performance of the seal layer and reduce the performance degradation caused by external factors. In order to improve the interface bonding effect between silicon carbide and other materials, specifically, according to the component volume ratio of 1:2, every 50g of silicon carbide powder is evenly placed in 100ml HCl with a concentration of 20%, and then deionized water is added to prepare 1L pickling solution. Add silicon carbide powder to the pickling solution, stir at a constant speed for 1 hour using a magnetic stirrer to allow the pickling solution to fully react with the silicon carbide surface. After stopping stirring, let the silicon carbide powder settle in the pickling solution for 1 hour, and then wash it with deionized water until the pH value of the washing solution reaches about 7. The washed silicon carbide powder is dried at high temperature in a blast drying oven to remove residual moisture, and then set aside.
[0030] Specifically, glass fibers can be interwoven in the surface emulsified asphalt to form a mesh structure, which can enhance the integrity of the seal layer, so that it is not easy to fall off or be damaged locally when subjected to external forces. At the same time, glass fibers can improve the toughness of the seal layer. When the road surface is slightly deformed, it can absorb energy through its own deformation and reduce the occurrence of cracks. Under the repeated load of vehicles, glass fibers can effectively alleviate the fatigue damage of the seal layer. In order to improve the interface bonding effect between glass fiber and other materials, the coupling agent γ-aminopropyltriethoxysilane is dissolved in ethanol at a concentration of 2%, and the glass fiber is immersed in the coupling agent solution at a mass ratio of 1:3. The immersion time is 1-4 hours, and the immersion temperature is between room temperature and 60°C. After immersion, take out the glass fiber and dry it naturally in a well-ventilated environment or dry it in an oven at 80-120°C for 1-2 hours to allow the coupling agent to fully react with the surface of the glass fiber and fix it.
[0031] Specifically, wollastonite has a fibrous crystal structure, which can fill the pores in the surface emulsified asphalt and improve the density of the seal. At the same time, it can also prevent the expansion of cracks to a certain extent and enhance the crack resistance of the seal. The chemical properties of wollastonite are stable, which can improve the stability of the seal under different environmental conditions. It can enhance the resistance of the seal to external factors such as moisture and chemicals, thereby extending the service life of the seal and enabling it to maintain good performance during long-term use. In order to improve the interface bonding effect between wollastonite and other materials, stearic acid is added to the ethanol aqueous solution. At a temperature of 50-60°C, stir at a speed of 400-500r / min for 30 minutes to completely dissolve the stearic acid. The weight ratio of wollastonite to stearic acid is 1:0.020, and 800 mesh wollastonite is added to the stearic acid ethanol aqueous solution. The reaction is carried out under sealed conditions. The reaction temperature is 80-90°C, the reaction time is 30 minutes, the stirring speed is 500-600r / min, and the reaction is cooled to room temperature. The precipitate was separated, washed twice with ethanol aqueous solution, cooled and washed, dried at 80°C, ground and sieved to obtain modified wollastonite.
[0032] The second filler can comprehensively improve the wear resistance, skid resistance, mechanical properties, stability and durability of the surface emulsified asphalt, thereby further improving the overall performance of the super-adhesive anti-skid seal layer.
[0033] The tackifier includes an epoxy tackifier resin and a thermoplastic elastomer, and the emulsifier is a fatty amine cationic emulsifier. The tackifier includes an epoxy tackifier resin and a thermoplastic elastomer. The tackifier can improve the adhesion and elastic recovery ability of asphalt, and can significantly improve the anti-rutting performance, durability and noise reduction effect of asphalt mixture.
[0034] Specifically, the tackifier used is the high-viscosity modifier PT-HVA for drainage asphalt pavement of Guolu New Materials, which includes epoxy-based tackifying resin and thermoplastic elastomer, which can effectively improve the absolute viscosity of asphalt, and has the characteristics of high softening point, high elastic recovery, high viscosity toughness, high anti-aging and the like. Furthermore, the epoxy-based tackifying resin has high adhesion and reactivity. Among the tackifiers, the epoxy-based tackifying resin can improve the bonding strength between the emulsified asphalt and the stone and the different structural layers, effectively prevent interlayer slippage, and ensure the integrity and stability of the pavement structure. In addition, the epoxy-based tackifying resin also has excellent heat resistance, chemical resistance and mechanical properties, making the emulsified asphalt difficult to soften and flow under high temperature conditions. Furthermore, thermoplastic elastomers give emulsified asphalt good elastic recovery properties, allowing the road surface to quickly return to its original state after being subjected to vehicle loads, reducing the accumulation of permanent deformation, and improving the impact resistance of the road surface. In low temperature environments, thermoplastic elastomers can maintain the flexibility of emulsified asphalt and prevent road cracking. Thermoplastic elastomers can improve the rheological properties of emulsified asphalt, making it easier to apply and compact during construction, thereby improving construction efficiency and quality.
[0035] The emulsifier is a fatty amine cationic emulsifier. The fatty amine cationic emulsifier is prepared by reacting palmitic acid with 1,3-propylenediamine, comprising the following steps: Q1: Dissolve palmitic acid in xylene solvent to form a solution, add p-toluenesulfonic acid as a catalyst to the solution to promote the esterification reaction, heat the mixture to a reflux temperature of 110-120°C, and continue stirring to allow the palmitic acid to completely dissolve and undergo esterification. After the reaction is completed, cool to room temperature, filter to remove unreacted solid impurities, and obtain a fatty acid ester solution; Q2: Heat the fatty acid ester solution to 80-100°C, slowly drop 1,3-propylenediamine into the fatty acid ester solution while continuing to stir, heat the mixture to 120-150°C, and continue to stir to carry out the amidation reaction; Q3: After the reaction is completed, cool to room temperature and wash with deionized water several times to remove unreacted 1,3-propylenediamine and other impurities.
[0036] Specifically, the fatty amine cationic emulsifier of the present invention has a lipophilic group and a hydrophilic group. The lipophilic group can combine with asphalt, and the hydrophilic group can interact with water. Through the action of mechanical forces such as high-speed shearing, the asphalt is evenly dispersed in the water in the form of tiny particles, and a stable emulsion system is formed. Furthermore, the cationic emulsifier will be adsorbed on the surface of the asphalt particles in the emulsion, so that the asphalt particles have a positive charge. Since the same charges repel each other, this electrostatic repulsion can prevent the asphalt particles from aggregating with each other, thereby improving the stability of the emulsion and extending the storage time of the emulsified asphalt.
[0037] In addition, in asphalt pavement construction, the use of fatty amine cationic emulsifiers can significantly reduce the viscosity of asphalt, making it easier to spread, compact and solidify, thereby improving construction efficiency. Fatty amine cationic emulsifiers can enhance the adhesion between asphalt and substrates such as stone, and improve the durability and resistance to water damage of the pavement. Compared with other types of emulsifiers, fatty amine cationic emulsifiers have lower environmental pollution and meet environmental protection requirements.
[0038] The stabilizer includes one or both of a polyvinyl alcohol solution and a polyacrylamide solution. Specifically, the stabilizer includes a polyvinyl alcohol solution with a mass fraction of 0.5-2% and a polyacrylamide solution with a mass fraction of 0.1-1%.
[0039] Specifically, polyvinyl alcohol molecules can adsorb on the surface of polymer particles and form a protective film, which helps prevent agglomeration and precipitation between particles. By reducing the interfacial tension in the system, polyvinyl alcohol helps to enhance the stability of the emulsion. The addition of polyvinyl alcohol solution can increase the viscosity of the entire system, thereby further stabilizing the emulsion. Polyvinyl alcohol contains a large number of hydroxyl groups on the molecular chain, which can form hydrogen bonds with asphalt molecules and stone surfaces. When emulsified asphalt is used in road construction, this hydrogen bonding helps to enhance the bonding force between the emulsified asphalt and the stone, making the road surface structure more solid and reducing the possibility of interlayer peeling.
[0040] Specifically, polyacrylamide has good flocculation properties and can connect asphalt particles together to form a three-dimensional network structure through the extension and entanglement of molecular chains. This structure can enhance the shear resistance of emulsified asphalt, so that it can maintain the integrity of the emulsion when subjected to external forces. At the same time, this three-dimensional network structure also helps to improve the stability of the emulsion and reduce the sedimentation of asphalt particles.
[0041] The crosslinking agent includes terephthalate and dimethoxymethane.
[0042] Specifically, terephthalate glycol can undergo cross-linking reaction with active groups (such as hydroxyl, carboxyl, etc.) in emulsified asphalt. This cross-linking reaction will form a three-dimensional network structure inside the emulsified asphalt, which can improve the cohesion and bonding strength of the emulsified asphalt. Terephthalate glycol also has a certain antibacterial effect and can inhibit the reproduction and growth of microorganisms such as bacteria and fungi, which helps to extend the storage effect and service life of emulsified asphalt and reduce maintenance costs. After adding terephthalate glycol to emulsified asphalt, its crack resistance, rutting resistance and durability can be significantly improved. In a high temperature environment, due to its three-dimensional network structure, the movement of the molecular chain of the cross-linked emulsified asphalt is restricted, and it is not easy to soften and flow, which can maintain the flatness of the road surface and improve the high temperature resistance of the road surface.
[0043] Specifically, the methoxy group in the chemical structure of dimethoxymethane can react with the hydroxyl or acid group in the polymer chain to form a cross-linked structure. This cross-linked structure can significantly improve the thermal stability and chemical resistance of the material, allowing the emulsified asphalt to maintain stable performance under high temperature or harsh environment. Dimethoxymethane can react with the components in the emulsified asphalt to promote the curing process of the emulsified asphalt. After road construction, when the water evaporates, it can speed up the drying speed of the emulsified asphalt, allowing the road surface to reach the strength requirements for opening to traffic more quickly.
[0044] As the water evaporates continuously, the asphalt particles in the emulsified asphalt begin to aggregate and form a continuous asphalt film. P-phenylene glycol and dimethoxymethane can play a synergistic role in the modified super-viscous emulsified asphalt. The three-dimensional network structure constructed by p-phenylene glycol provides a basic strength and stability framework for the emulsified asphalt, which can increase the softening point of the asphalt, thereby improving the stability of the asphalt under high temperature conditions, while dimethoxymethane can increase the disorder of the carbon layer and the surface defects, play a role in promoting curing and chemical resistance. The combination of the two can significantly improve the strength, stability, aging resistance, water resistance and chemical corrosion resistance of the emulsified asphalt.
[0045] The crushed stone layer includes one or both of basalt and diabase. The particle size of the crushed stone layer is 1.18-4.75 mm.
[0046] Basalt has high compressive strength and hardness, which can effectively improve the structural stability of the road surface. Basalt fiber can be used in asphalt gravel seal, which can significantly improve the wear resistance of the road surface and reduce the wear caused by traffic load. Basalt fiber has good adsorption and absorption of asphalt, which can disperse stress and improve the flexibility of the road surface, thereby enhancing the high temperature rutting resistance and low temperature crack resistance of the asphalt pavement. Basalt fiber has excellent properties such as high temperature resistance, oxidation resistance, and radiation resistance, and is suitable for pavement engineering in various environments. Due to its small porosity, diabase also helps to improve the overall density of the road surface. Diabase has good chemical corrosion resistance and can improve the durability of the road surface. The particle shape of diabase gravel is also mostly irregular, which helps to form a tight interlocking structure in the gravel layer, and improves the stability of the gravel layer by mutual support and fixation. The mixed use of basalt and diabase gravel can make the gravel layer more dense and have a smaller porosity. This can not only improve the bearing capacity of the crushed stone layer, but also reduce the amount of bonding materials used, reduce costs, and enhance the wear resistance, compression resistance, anti-skid and chemical stability of the crushed stone layer of the super-adhesive anti-skid seal layer.
[0047] The auxiliary agent includes an anti-stripping agent, an antioxidant, a plasticizer, and a pH regulator. The anti-stripping agent is at least one of calcium stearate and zinc acetate, the antioxidant is β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, the plasticizer is alkyl sulfonate phenyl ester, and the pH regulator includes hydrochloric acid and sodium hydroxide. In addition, the plasticizer can increase the flexibility and ductility of the coating, reduce its brittleness, and help improve the comprehensive performance of the coating. Further, the anti-stripping agent can increase the adhesion between the coating and the base surface and prevent the occurrence of peeling. Further, the antioxidant can delay the aging process of the coating and improve its durability. Further, the pH regulator can adjust the pH value of the emulsion to ensure its stability.
[0048] The anti-stripping agent is at least one of calcium stearate and zinc acetate, the antioxidant is β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, the plasticizer is alkyl sulfonate phenyl ester, and the pH adjuster includes hydrochloric acid and sodium hydroxide.
[0049] Specifically, calcium stearate can form a chemical bond with the surface of stone in asphalt, enhance the adhesion between asphalt and stone, effectively prevent asphalt from peeling off the stone surface, improve the durability of the road surface, and enhance the splitting tensile strength and water damage resistance of the asphalt mixture.
[0050] Specifically, zinc acetate can improve the hydrophilicity of the stone surface, enhance the adhesion between emulsified asphalt and acidic stone, help enhance the adhesion and durability of the material, prevent coating peeling, and increase the service life of the material.
[0051] Specifically, β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate can inhibit the oxidation reaction of asphalt, delay the aging process of emulsified asphalt during use, maintain the adhesion and waterproofness of emulsified asphalt, and thus extend the service life of the road surface.
[0052] Specifically, alkyl phenyl sulfonate can reduce the glass transition temperature of emulsified asphalt, improve its flexibility and low-temperature performance, make emulsified asphalt easier to apply and shape during construction, improve construction efficiency, reduce cracks in the road surface caused by low temperatures, improve the frost resistance of the road surface, and enhance the plasticity of emulsified asphalt, so that it can better adapt to the deformation of the road surface and reduce the stress concentration of the road surface under vehicle load. It has high saponification resistance, can protect the coating even after a long period of cleaning, and has very good compatibility with polymers.
[0053] Specifically, hydrochloric acid, as an acidic regulator, can lower the pH value of water to prevent the emulsification effect and stability from being affected by excessive alkalinity. Sodium hydroxide, as an alkaline regulator, can increase the pH value of water, which helps to adjust the hardness of water and the optimal pH value for emulsified asphalt.
[0054] Furthermore, another object of the present invention is to provide a construction method of a super-adhesive anti-slip seal layer, comprising the following steps: S1. Process the original road markings and clean the original road surface; specifically, the thickness of the CDP super-sticky anti-skid seal is relatively small, and its main function is to improve the anti-skid coefficient of the road surface. It has certain requirements for the road surface structural strength, road surface condition and road surface flatness, especially requiring the road surface to have a certain flatness. For sections where the road surface structural strength, road surface condition and road surface flatness meet the requirements, there may be road surface diseases such as cracks, potholes, rutting, etc. It is necessary to further propose constraints and corresponding disease treatment methods to ensure the durability of the CDP super-sticky anti-skid seal. Specifically, the original road surface structural strength should meet the normal driving requirements, and the rutting depth should be less than 10mm; structural diseases such as subsidence, potholes, and bumps have been treated.
[0055] When cleaning the original road surface, clean the lower working surface and use a hair dryer to blow away the dust on the road surface. When processing the original road markings, use colored strips to cover the text, arrows, and horizontal deceleration markings for anti-pollution treatment. For the longitudinal deceleration markings, set a baffle on the side of the nozzle for anti-pollution treatment. For the starting and ending ends of the construction section, use colored strips to cover for anti-pollution treatment, with a treatment range of 3 to 5m. For the expansion joint structure, use hemp rope for internal filling and colored strips for top covering; the concrete part is directly sprinkled.
[0056] S2. Loading and debugging related parameters; the length of the test section shall not be less than 50m. Based on the preliminarily determined construction plan, the spraying amount, aggregate spreading amount, and construction process shall be verified and adjusted through the test section to verify whether the construction equipment, various technical parameters, and construction effects meet the requirements, and determine the final construction plan and mix ratio. In addition, the amount of emulsified asphalt, crushed stone, and emulsified asphalt in the bottom layer shall be preliminarily determined. According to the calculated upper and lower limits, materials can be prepared and stored quickly, so that sufficient materials can be reserved in time for subsequent adjustments.
[0057] S3. Calculate the amount of bottom emulsified asphalt and gravel on site, and spread the bottom emulsified asphalt and gravel; specifically, the spreading speed is controlled at 50-100 m / min. The spreading amount of super-viscous emulsified asphalt is 0.9-1.2 kg / m 2 , the amount of crushed stone spread is 4.0~5.5kg / m 2 , the coverage rate of crushed stone is 100% to 110%. The super-viscous emulsified asphalt for super-viscous anti-skid crushed stone seal can be used at room temperature, but in cold weather, the heating system of the sealing vehicle should be turned on to properly heat the super-viscous emulsified asphalt for CDP super-viscous anti-skid crushed stone seal, and the temperature should be controlled at 40 to 60°C.
[0058] S4: Curing and rolling; After the super-sticky modified emulsified asphalt and gravel are spread, they should be cured for 2 to 3 hours. After the base oil is spread, check the emulsified asphalt demulsification of the working surface 1 to 2 hours later. The rolling process is carried out based on the intuitive judgment standard of non-stickiness. Use an 8t rubber-wheeled roller for rolling, 2 times, and a rolling speed of 15 to 20 km / h. The width of one wheel should be controlled at 20 to 30 cm for back and forth compaction and overlapping rolling. The flatness should be checked after the initial rolling. If there are serious defects, repair or even rework should be carried out. The residual material can be recovered 15 to 30 minutes after the rolling is completed. The residual material recovery speed is controlled at 3 to 6 km / h. After the residual material is recovered, it should be ensured that there is no loose gravel in the bottom layer.
[0059] S5. Calculate the amount of surface emulsified asphalt on site and spread it. The surface emulsified asphalt is controlled according to the test road parameters, generally 0.4-0.6 kg / m 2 The width of the surface oil must be consistent with the width of the base oil and gravel, and the line shape must be consistent.
[0060] S6: Curing: After spreading, cure for 1 to 2 hours. The visual judgment standard is whether the surface of the seal layer is not sticky and the aggregate is firmly bonded.
[0061] S7: Restore the markings and open to traffic. In summer, the surface oil should be maintained for 2 to 3 hours after spreading to make the road surface dry; in autumn and winter, ensure that the emulsified asphalt is completely demulsified and the surface is dry and solidified before allowing traffic.
[0062] Specifically, when the road surface temperature is ≥25°C, the curing time is 2 to 4 hours, and when the road surface temperature is <25°C, the curing time is 3 to 6 hours. By calculating the amount of emulsified asphalt and crushed stone separately in the room, the relationship between the set material dosage parameters and the actual material dosage is established to accumulate data for subsequent construction. By calculating the amount of emulsified asphalt and crushed stone on site and making dynamic adjustments, the amount of spreading can be ensured to be within a controllable range.
[0063] The emulsified asphalt of the present invention has good permeability and can effectively penetrate into the old road surface; the emulsified asphalt can improve the adhesion between asphalt and aggregate and effectively prevent the stone from falling off; the emulsified asphalt has a high softening point, high temperature stability and anti-rutting performance, so as to ensure the high temperature deformation resistance of the asphalt mixture and improve the stability of the asphalt concrete at high temperature; the emulsified asphalt has excellent elastic recovery and excellent plastic deformation ability, so as to improve the crack resistance of the asphalt mixture under high stress; the emulsified asphalt has a faster curing speed, and the super-viscous emulsified asphalt after rapid curing can form a non-stick wheel protective film to improve the early wheel sticking phenomenon of the new maintenance layer and shorten the opening traffic time; the emulsified asphalt has excellent road performance, and the super-viscous emulsified asphalt should ensure the surface strength, wear resistance, high and low temperature resistance and aging resistance of the sealing layer, and can significantly extend the service life of the road surface.
[0064] Specifically, the preliminary determination amount in step S2 is obtained according to the following steps: S201. Place two sample trays in a group between the wheels of the synchronous gravel sealer in the direction of travel to collect the emulsified asphalt and gravel spread during the construction process. The distance between the first sample trays of each group shall be no less than 200m, and there shall be no less than 3 points in each construction section to monitor the material consumption of the whole process; the sample tray size is an iron tray with a length × width × height of 10cm × 10cm × 2cm; S202, placing the sample tray with known mass m0 as described in step S201; S203. After the synchronous chip seal vehicle passes at a uniform speed, take out the sample tray and clean the emulsified asphalt material on the outer wall with a clean rag, and then weigh and record it as m1, accurate to 0.1g; S204. Calculate the total amount of emulsified asphalt and crushed stone spread to obtain the total amount of emulsified asphalt and crushed stone spread in each sample tray: SD E+S =0.1×(m1-m0), where: SD E+S —Total amount of emulsified asphalt and crushed stone spread on the bottom layer, kg / m 2 .
[0065] S205, placing the weighed sample tray aside for drying, or sending it to a laboratory for testing as soon as possible; at the same time, collecting gravel for testing moisture content; S206. Place the sample tray containing the emulsified asphalt and crushed stones in an oven at 180-190°C and heat for 60 minutes. Then use a small spatula to shovel all the crushed stones in the sample tray into the beaker, making sure that all the crushed stones are shoveled in. S207. After the temperature of the material in the beaker returns to room temperature, add enough trichloroethylene, soak for about 2 hours, and sieve with a 0.075mm sieve. Repeat the soaking and sieving process until the trichloroethylene solution is observed to be white and transparent, which means that the asphalt is completely dissolved; S208. Put the sieved gravel and the sieve into an oven, set the temperature to 120°C, and heat for no less than 30 minutes. Then take out the sample, cool it, and finally weigh the mass m2 of the gravel in the sieve.
[0066] S209. Test the water content ω of gravel according to the test method T0801-2009 in the standard JTGE51-2009.
[0067] Calculation of gravel spreading amount: SD S =0.1×m2(1+ω) SD E =SD E+S -SD S In the formula: SDE+S —Total amount of emulsified asphalt and crushed stone spread on the bottom layer, kg / m 2 .
[0068] SD S — Crushed stone spreading amount, kg / m 2 .
[0069] SD E —Amount of emulsified asphalt spread on the bottom layer, kg / m 2 .
[0070] The final result is the average value of the calculated results for each sample plate. If it exceeds the designed amount, timely adjustments must be made.
[0071] Specifically, the spreading amount in steps S3 and S5 is obtained according to the following steps: S301. Place two sample trays in a group between the wheels of the synchronous gravel sealer in the direction of travel to collect the emulsified asphalt and gravel spread during the construction process. The distance between the first sample trays of each group shall be no less than 200m, and there shall be no less than 3 points in each construction section to monitor the material consumption of the whole process; the sample tray size is an iron tray with a length × width × height of 10cm × 10cm × 2cm; S302, weigh the mass of each sample tray with an electronic scale and record it as m0, accurate to 0.1g, and place the sample tray with known mass m0 as described in step S301; S303. After the synchronous chip seal vehicle passes at a uniform speed, take out the sample tray and clean the emulsified asphalt material on the outer wall with a clean rag, and then weigh and record it as m1, accurate to 0.1g.
[0072] S304. Calculation of total spreading amount of bottom emulsified asphalt and crushed stone: SD E+S =0.1×(m1-m0), where: SD E+S —Total amount of emulsified asphalt and crushed stone spread on the bottom layer, kg / m 2, The final result is the average value of the calculated results for each sample plate. If it exceeds the designed amount, timely adjustments must be made.
[0073] S305, according to the above steps, two sample trays are grouped together and placed between the wheels of the synchronous chip sealer in the direction of travel to collect the emulsified asphalt spread during the construction process, and a sample tray m2 containing the surface emulsified asphalt is obtained; S306. Calculate the amount of emulsified asphalt spread for the second surface layer, SD E =0.1×(m2-m0), where: SDE—spreading amount of emulsified asphalt, kg / m 2 The final result is the average value of the calculated results for each sample plate. If it exceeds the designed amount, timely adjustments must be made.
[0074] Furthermore, another object of the present invention is to provide an application of a super-adhesive anti-slip sealing layer, wherein the super-adhesive anti-slip sealing layer is applied in the preventive maintenance construction of the super-adhesive anti-slip sealing layer.
[0075] The present invention uses a synchronous chip sealer to evenly spread super-viscous emulsified asphalt and single-size crushed stones on the road surface at room temperature to form a crushed stone seal with a "two oils and one stone" sandwich structure. The bottom super-viscous emulsified asphalt provides excellent bonding strength between the stone and the original road surface, and the surface super-viscous emulsified asphalt ensures excellent coating of the crushed stones, effectively compensating for the problems of overall shedding and crushed stone falling in conventional chip seal technology, thereby ensuring the long-term effectiveness of the CDP super-viscous anti-skid seal preventive maintenance technology and extending the service life of the road surface.
[0076] Specifically, the anti-skid seal technology of the present invention is a new preventive maintenance technology with a thickness of 4 to 5 mm. Under normal temperature, a dedicated intelligent precision-controlled synchronous seal vehicle is used to spread the bottom layer of emulsified asphalt and stone (2 to 4 mm) to form a base layer, which is rolled using a small roller, and then the surface layer of emulsified asphalt (1 to 2 mm) is spread on this basis and solidified on the original asphalt pavement to form a highly wear-resistant and anti-skid structure.
[0077] Compared with the prior art, the present invention has the following advantages: 1. The formula design of the present invention is reasonable, and the ratio between the raw materials is moderate, which can give full play to their respective roles and improve the comprehensive performance of emulsified asphalt. The bottom emulsified asphalt of the present invention has excellent film-forming, adhesion, and waterproof properties, which not only improves the interlayer bonding ability, but also enhances the durability of use. The surface emulsified asphalt of the present invention can comprehensively improve the wear resistance, skid resistance, mechanical properties, stability and durability of the surface emulsified asphalt, thereby further improving the overall performance of the super-sticky anti-skid seal layer. The super-sticky anti-skid seal layer of the present invention has excellent adhesion, waterproofness and durability, is suitable as a road engineering material, and can meet application scenarios with different needs.
[0078] 2. The construction method of the present invention can improve the performance of the functional layer of the asphalt pavement, significantly improve the anti-skid performance and water-sealing performance of the pavement, and extend the service life of the pavement; at the same time, compared with traditional maintenance processes, the maintenance cost is lower, the cycle is shorter, the amount of stone used is less, and construction can be carried out at room temperature, with excellent economic and environmental benefits. The construction method of the present invention can improve the anti-skid performance and increase the friction coefficient of the pavement by more than 30%; the construction road closure time is short, and traffic can be opened on the day of construction.
[0079] 3. The application of the super-adhesive anti-skid seal layer of the present invention in preventive maintenance construction can effectively improve the anti-skid performance and durability of the road surface, thereby extending the service life of the road and improving driving safety. DETAILED DESCRIPTION
[0080] In order to make those skilled in the art more clearly understand the technical solution of the present invention, the following examples are listed for illustration. Unless otherwise specified, the raw materials, reagents or devices used in the following embodiments can be obtained from conventional commercial channels or can be obtained by existing known methods.
[0081] The present invention will be further described below in conjunction with specific embodiments: The modified silica is silica modified with γ-(2,3-epoxypropoxy)propyltrimethoxysilane. The preparation steps of silica modified with γ-(2,3-epoxypropoxy)propyltrimethoxysilane are as follows: N1, nano-silica was dried at 100°C for 2 hours to remove the moisture adsorbed on the surface and then cooled to room temperature; N2. Prepare γ-(2,3-epoxypropoxy)propyltrimethoxysilane-ethanol solution with a γ-(2,3-epoxypropoxy)propyltrimethoxysilane concentration of 1%. Use hydrochloric acid to adjust the pH value of the solution to 3. Add the dried silica to the silane solution, heat the mixture to 50°C, and continue stirring for 3 hours.
[0082] N3. Filter the modified silica, wash it with anhydrous ethanol and deionized water for several times, and dry the washed silica at 80° C. for 4 hours until it is completely dry to obtain γ-(2,3-epoxypropoxy)propyltrimethoxysilane-modified silica.
[0083] The polypropylene composite particles adopt VLF 80107 CC of RTP of the United States.
[0084] The modified montmorillonite is montmorillonite modified by hexadecyltrimethylammonium bromide, and the preparation method of the modified montmorillonite is as follows: M1: 2 g of sodium montmorillonite was dissolved in deionized water, and a montmorillonite suspension with a mass concentration of 2% was obtained under stirring. The cation exchange capacity of the sodium montmorillonite was 100 meq / 100 g; M2: Add hexadecyltrimethylammonium bromide to deionized water, stir evenly, prepare hexadecyltrimethylammonium bromide solution, adjust pH value to 6-8, the amount of hexadecyltrimethylammonium bromide is 2 mol / meq montmorillonite exchange capacity; M3: Slowly add hexadecyltrimethylammonium bromide to the exfoliated montmorillonite suspension. The reaction temperature is controlled at 100°C and the reaction time is 210 minutes; M4: The reaction product is centrifuged and washed 2-5 times to remove unreacted hexadecyltrimethylammonium bromide and other impurities, and dried at 70-80°C for 12-18 hours to remove moisture and residual solvent.
[0085] The modified carbon nanotubes are polyaniline-modified carbon nanotubes. The preparation method of polyaniline-modified carbon nanotubes comprises the following steps: P1. Add 0.5 g of aniline monomer into 100 ml of deionized water, stir evenly to prepare an aniline solution of a certain concentration, and adjust the pH value of the aniline solution to 2-3 with hydrochloric acid to promote the protonation of aniline; P2, dispersing 100 mg of multi-walled carbon nanotubes in 100 ml of deionized water, using an ultrasonic disperser for 30 minutes, and washing the dispersed carbon nanotubes with deionized water several times; P3. Add the dispersed carbon nanotubes to the aniline solution, stir for 60 minutes at room temperature using a magnetic stirrer or a mechanical stirrer to obtain a mixed solution, dissolve 0.5 g of ammonium persulfate in a small amount of deionized water, and then slowly add the mixed solution to the mixed solution; cool the mixed solution to 5° C. in an ice bath, and continue stirring for 8 hours; P4. Filter the modified carbon nanotubes, wash them with deionized water and anhydrous ethanol for multiple times, and dry the washed carbon nanotubes at 80° C. for 4 hours until they are completely dry.
[0086] The second filler includes at least three of ultra-high molecular weight polyethylene, basalt particles, silicon carbide, glass fiber, and wollastonite. The processing method includes the following steps: The ultra-high molecular weight polyethylene particles were placed in a ball mill, and grinding media steel balls were added, and the ball milling was performed at a rotation speed of 300 r / min for 5 hours.
[0087] According to the volume ratio of 1:2, every 50g of silicon carbide powder is evenly placed in 100ml HCl with a concentration of 20%, and then deionized water is added to prepare 1L of pickling solution. Add silicon carbide powder to the pickling solution and stir it at a constant speed for 1 hour using a magnetic stirrer to allow the pickling solution to fully react with the silicon carbide surface. After stopping stirring, let the silicon carbide powder settle in the pickling solution for 1 hour, and then wash it with deionized water until the pH value of the washing solution reaches about 7. Dry the washed silicon carbide powder at high temperature in a blast drying oven to remove residual moisture, and then set it aside.
[0088] Dissolve 2% coupling agent γ-aminopropyltriethoxysilane in ethanol, and soak the glass fiber in the coupling agent solution at a mass ratio of 1:3 for 3 hours at a temperature of 50°C. After soaking, take out the glass fiber and dry it naturally in a well-ventilated environment or in an oven at 80°C for 2 hours.
[0089] Add stearic acid to ethanol aqueous solution, stir at 500r / min for 30 minutes at a temperature of 60°C to completely dissolve the stearic acid. The weight ratio of wollastonite to stearic acid is 1:0.020. Add 800 mesh wollastonite to stearic acid ethanol aqueous solution and react under sealed conditions. Reaction temperature 80°C, reaction time 30 minutes, stirring speed 500r / min, cool to room temperature after reaction. Separate the precipitate and wash the precipitate twice with ethanol aqueous solution. Cool and wash, and dry at 80°C. Grind and sieve to obtain modified wollastonite.
[0090] The emulsifier is a fatty amine cationic emulsifier. The fatty amine cationic emulsifier is prepared by reacting palmitic acid with 1,3-propylenediamine, comprising the following steps: Q1: Dissolve 50g of palmitic acid in 100mL of xylene solvent to form a solution, add 0.5g of p-toluenesulfonic acid as a catalyst to the solution, heat the mixture to a reflux temperature of 120°C, and continue stirring. After the reaction is completed, cool to room temperature, filter to remove unreacted solid impurities, and obtain a fatty acid ester solution; Q2: Heat the above fatty acid ester solution to 100°C, slowly drop 15g of 1,3-propylenediamine into the fatty acid ester solution while continuing to stir, heat the mixture to 120°C, and continue to stir; Q3: After the reaction is completed, cool to room temperature and wash with deionized water for several times to remove unreacted propylene diamine and other impurities to obtain a fatty amine cationic emulsifier.
[0091] The viscosity enhancer used is Guolu New Materials' high viscosity modifier for drainage asphalt pavement PT-HVA.
[0092] The stabilizer includes one or both of a 1% by mass polyvinyl alcohol solution and a 0.5% by mass polyacrylamide solution.
[0093] The preparation method of bottom emulsified asphalt comprises the following steps: J1. Stir corresponding amounts of stabilizer, part of water and part of emulsifier at 50-60° C. with a high-speed stirrer at 400-600 rpm for 1-5 min to obtain a first mixed solution, adjust the pH value to 2-3 with a pH adjuster, add an anti-stripping agent and an antioxidant to the first mixed solution, and stir with a high-speed stirrer at 400-600 rpm for 5-10 minutes to obtain a basic soap solution; J2. Heat the base asphalt to 130-180° C., add a corresponding amount of asphalt modifier by mass, and stir at 800-1200 rpm for 30-60 minutes using a high-speed mixer to obtain a modified base asphalt; J3. Slowly add the modified matrix asphalt into the base soap solution, and use a high-speed shear emulsifier for emulsification at a shear speed of 3000-5000 rpm for an emulsification time of 10-30 minutes to obtain an emulsified asphalt intermediate; J4, stirring the corresponding mass parts of tackifier, plasticizer, remaining water and remaining emulsifier at 50-60° C. with a high-speed stirrer at 800-1200 rpm for 20-50 minutes to obtain a second mixed solution; J5. Add the first filler of corresponding mass parts to the emulsified asphalt intermediate, stir the mixture at 800-1200 rpm for 30-60 minutes using a high-speed stirrer, add the second mixed solution and continue stirring at 800-1200 rpm for 10-30 minutes, adjust the pH value to 2-5 using a pH adjuster, then add the cross-linking agent, and continue stirring at 800-1200 rpm for 10-30 minutes to obtain a bottom emulsified asphalt.
[0094] The preparation method of surface emulsified asphalt comprises the following steps: K1. Stir corresponding amounts of stabilizer, part of water and part of emulsifier at 50-60° C. with a high-speed stirrer at 400-600 rpm for 1-5 min to obtain a first mixed solution, adjust the pH value to 2-3 with a pH adjuster, add an anti-stripping agent and an antioxidant to the first mixed solution, and stir with a high-speed stirrer at 400-600 rpm for 5-10 minutes to obtain a basic soap solution; K2, heating the base asphalt to 130-180° C., adding a corresponding amount of asphalt modifier by mass, and stirring at 800-1200 rpm for 30-60 minutes using a high-speed mixer to obtain a modified base asphalt; K3, slowly adding the modified matrix asphalt into the base soap solution, and simultaneously using a high-speed shear emulsifier for emulsification at a shear speed of 3000-5000 rpm for an emulsification time of 10-30 minutes to obtain an emulsified asphalt intermediate; K4, stirring corresponding weight portions of tackifier, plasticizer, remaining water, and remaining emulsifier at 50-60° C. with a high-speed stirrer at 800-1200 rpm for 20-50 minutes to obtain a second mixed solution; K5. Add the second filler of corresponding mass parts to the emulsified asphalt intermediate, stir it at 800-1200 rpm for 30-60 minutes using a high-speed stirrer, add the second mixed liquid and continue stirring at 800-1200 rpm for 10-30 minutes, adjust the pH value to 2-5 using a pH adjuster, then add the cross-linking agent, and continue stirring at 800-1200 rpm for 10-30 minutes to obtain the surface emulsified asphalt.
[0095] Table 1: Weight composition ratio of base emulsified asphalt formula
[0096] Table 2: Weight composition ratio of surface emulsified asphalt formula
[0097] Example 1 A method for preparing bottom emulsified asphalt comprises the following steps: J1. Stir corresponding parts of stabilizer, 20 parts of water and 2 parts of emulsifier at 50-60° C. with a high-speed stirrer at 600 rpm for 1 min to obtain a first mixed solution, adjust the pH value to 2 with a pH adjuster, add an anti-stripping agent and an antioxidant to the first mixed solution, and stir with a high-speed stirrer at 400 rpm for 5 minutes to obtain a basic soap solution; J2. Heat the base asphalt to 130° C., add a corresponding amount of asphalt modifier by mass, and stir at 800 rpm for 30 minutes using a high-speed mixer to obtain a modified base asphalt; J3. Slowly add the modified matrix asphalt into the base soap solution, and use a high-speed shear emulsifier for emulsification at a shear speed of 3000 rpm for 10 minutes to obtain an emulsified asphalt intermediate; J4, stirring the corresponding mass parts of tackifier, plasticizer, remaining water and remaining emulsifier at 50° C. and 800 rpm in a high-speed stirrer for 20 minutes to obtain a second mixed solution; J5. Add the filler in corresponding parts by mass to the emulsified asphalt intermediate, stir the mixture at 800 rpm for 30 minutes using a high-speed stirrer, add the second mixed solution and continue stirring at 800 rpm for 10 minutes, adjust the pH value to 2 using a pH adjuster, then add the cross-linking agent, and continue stirring at 800 rpm for 10 minutes to obtain a bottom emulsified asphalt.
[0098] Example 2 A method for preparing bottom emulsified asphalt comprises the following steps: J1. Stir corresponding parts of stabilizer, 30 parts of water and 2 parts of emulsifier at 60° C. with a high-speed stirrer at 600 rpm for 5 min to obtain a first mixed solution, adjust the pH value to 3 with a pH adjuster, add an anti-stripping agent and an antioxidant to the first mixed solution, and stir with a high-speed stirrer at 600 rpm for 10 minutes to obtain a basic soap solution; J2. Heat the base asphalt to 150° C., add a corresponding amount of asphalt modifier by mass, and stir at 1200 rpm for 60 minutes using a high-speed mixer to obtain a modified base asphalt; J3. Slowly add the modified matrix asphalt into the base soap solution, and use a high-speed shear emulsifier to emulsify it at the same time, with a shear speed of 5000 rpm and an emulsification time of 30 minutes to obtain an emulsified asphalt intermediate; J4, stirring the corresponding mass parts of tackifier, plasticizer, remaining water and remaining emulsifier at 60° C. and 1200 rpm in a high-speed stirrer for 50 minutes to obtain a second mixed solution; J5. Add the filler in corresponding parts by mass to the emulsified asphalt intermediate, stir the mixture at 1200 rpm for 60 minutes using a high-speed stirrer, add the second mixed solution and continue stirring at 1200 rpm for 30 minutes, adjust the pH value to 2 using a pH adjuster, then add the cross-linking agent, and continue stirring at 1200 rpm for 30 minutes to obtain a bottom emulsified asphalt.
[0099] Example 3 A method for preparing bottom emulsified asphalt comprises the following steps: J1. Stir corresponding parts of stabilizer, 20 parts of water and 2 parts of emulsifier at 50-60° C. with a high-speed stirrer at 500 rpm for 3 min to obtain a first mixed solution, adjust the pH value to 2 with a pH adjuster, add an anti-stripping agent and an antioxidant to the first mixed solution, and stir with a high-speed stirrer at 500 rpm for 7 minutes to obtain a basic soap solution; J2. Heat the base asphalt to 180° C., add a corresponding amount of asphalt modifier by mass, and stir at 1000 rpm for 40 minutes using a high-speed mixer to obtain a modified base asphalt; J3. Slowly add the modified matrix asphalt into the base soap solution, and use a high-speed shear emulsifier to emulsify it at the same time. The shear speed is 4000 rpm and the emulsification time is 40 minutes to obtain an emulsified asphalt intermediate; J4, stirring corresponding parts by mass of tackifier, plasticizer, remaining water and remaining emulsifier at 55° C. and 1000 rpm in a high-speed stirrer for 40 minutes to obtain a second mixed solution; J5. Add the filler of corresponding mass parts to the emulsified asphalt intermediate, stir at 1000 rpm for 40 minutes using a high-speed stirrer, add the second mixed liquid and continue stirring at 1000 rpm for 40 minutes, adjust the pH value to 3 using a pH adjuster, then add the cross-linking agent, and continue stirring at 1000 rpm for 40 minutes to obtain a bottom emulsified asphalt.
[0100] Example 4 A method for preparing bottom emulsified asphalt comprises the following steps: J1. Stir corresponding parts of stabilizer, 25 parts of water and 1.5 parts of emulsifier at 50°C with a high-speed stirrer at 400 rpm for 1 min to obtain a first mixed solution, adjust the pH value to 2 with a pH adjuster, add an anti-stripping agent and an antioxidant to the first mixed solution, and stir with a high-speed stirrer at 500 rpm for 5 minutes to obtain a basic soap solution; J2. Heat the base asphalt to 160° C., add a corresponding amount of asphalt modifier by mass, and stir the mixture at 900 rpm for 50 minutes using a high-speed mixer to obtain a modified base asphalt; J3. Slowly add the modified matrix asphalt into the base soap solution, and use a high-speed shear emulsifier to emulsify it at the same time, with a shear speed of 3000 rpm and an emulsification time of 50 minutes to obtain an emulsified asphalt intermediate; J4, stirring the corresponding mass parts of tackifier, plasticizer, remaining water and remaining emulsifier at 50° C. and 900 rpm in a high-speed stirrer for 30 minutes to obtain a second mixed solution; J5. Add the filler of corresponding mass parts to the emulsified asphalt intermediate, stir at 900 rpm for 50 minutes using a high-speed stirrer, add the second mixed liquid and continue stirring at 900 rpm for 20 minutes, adjust the pH value to 5 using a pH adjuster, then add the cross-linking agent, and continue stirring at 900 rpm for 20 minutes to obtain a bottom emulsified asphalt.
[0101] Example 5 A method for preparing bottom emulsified asphalt comprises the following steps: J1. Stir corresponding parts of stabilizer, 20 parts of water and 3 parts of emulsifier at 60° C. with a high-speed stirrer at 600 rpm for 5 min to obtain a first mixed solution, adjust the pH value to 3 with a pH adjuster, add an anti-stripping agent and an antioxidant to the first mixed solution, and stir with a high-speed stirrer at 400 rpm for 10 minutes to obtain a basic soap solution; J2. Heat the base asphalt to 130° C., add a corresponding amount of asphalt modifier by mass, and stir at 1100 rpm for 30 minutes using a high-speed mixer to obtain a modified base asphalt; J3. Slowly add the modified matrix asphalt into the base soap solution, and use a high-speed shear emulsifier for emulsification at a shear speed of 5000 rpm for 10 minutes to obtain an emulsified asphalt intermediate; J4, stirring the corresponding mass parts of tackifier, plasticizer, remaining water and remaining emulsifier at 60° C. and 1100 rpm in a high-speed stirrer for 20 minutes to obtain a second mixed solution; J5. Add the filler of corresponding mass parts to the emulsified asphalt intermediate, stir it at 1100 rpm for 30 minutes using a high-speed stirrer, add the second mixed liquid and continue stirring at 1100 rpm for 20 minutes, adjust the pH value to 4 using a pH adjuster, then add the cross-linking agent, and continue stirring at 1100 rpm for 20 minutes to obtain the bottom emulsified asphalt.
[0102] Example 6 Example 6 is a method for preparing surface emulsified asphalt. The preparation method of Example 6 is the same as that of Example 1. The difference between Example 6 and Example 1 is that the first filler is changed to a second filler.
[0103] Example 7 Example 7 is a method for preparing surface emulsified asphalt. The preparation methods of Example 7 and Example 2 are the same. The difference between Example 7 and Example 2 is that the first filler is changed to a second filler.
[0104] Example 8 Example 8 is a method for preparing surface emulsified asphalt. The preparation methods of Example 8 and Example 3 are the same. The difference between Example 8 and Example 3 is that the first filler is changed to a second filler.
[0105] Example 9 Example 9 is a method for preparing surface emulsified asphalt. The preparation methods of Example 9 and Example 4 are the same. The difference between Example 9 and Example 4 is that the first filler is changed to a second filler.
[0106] Example 10 Example 10 is a method for preparing surface emulsified asphalt. The preparation methods of Example 10 and Example 5 are the same. The difference between Example 10 and Example 5 is that the first filler is changed to a second filler.
[0107] Comparative Example 1 The main difference between Comparative Example 1 and Example 2 is that the asphalt modifier is completely replaced with styrene-butadiene-styrene block copolymer in Comparative Example 1. The remaining steps and component parameters of Comparative Example 1 are the same as those of Example 2.
[0108] Comparative Example 2 The main difference between Comparative Example 2 and Example 2 is that all fillers are replaced with commercially available silicon dioxide in Comparative Example 2. The remaining steps and component parameters of Comparative Example 2 are the same as those of Example 2.
[0109] Comparative Example 3 The main difference between Comparative Example 3 and Example 2 is that the tackifier and the crosslinking agent are omitted in Comparative Example 3. The remaining steps and component parameters of Comparative Example 3 are the same as those of Example 2.
[0110] Comparative Example 4 The main difference between Comparative Example 4 and Example 2 is that the emulsifier in Comparative Example 4 is replaced by commercially available octylphenol polyoxyethylene ether Triton x-100. The remaining steps and component parameters of Comparative Example 4 are the same as those of Example 2.
[0111] Comparative Example 5 The main difference between Comparative Example 5 and Example 2 is that the preparation method in Comparative Example 5 is modified as follows: A method for preparing bottom emulsified asphalt comprises the following steps: J1. Stir corresponding amounts of stabilizer, water and emulsifier at 60° C. with a high-speed stirrer at 600 rpm for 5 min to obtain a first mixed solution, adjust the pH value to 3 with a pH adjuster, add an anti-stripping agent, an antioxidant, a tackifier, a plasticizer, a first filler and a cross-linking agent to the first mixed solution, and stir at 600 rpm with a high-speed stirrer for 10 minutes to obtain a basic soap solution; J2. Heat the base asphalt to 150° C., add a corresponding amount of asphalt modifier by mass, and stir at 1200 rpm for 60 minutes using a high-speed mixer to obtain a bottom emulsified asphalt; J3. Slowly add the modified matrix asphalt into the base soap solution and use a high-speed shear emulsifier to emulsify it at a shear speed of 5000 rpm and an emulsification time of 30 minutes to obtain a bottom emulsified asphalt.
[0112] The component parameters of Comparative Example 5 are the same as those of Example 2.
[0113] Comparative Example 6 The main difference between Comparative Example 6 and Example 7 is that the asphalt modifier is completely replaced with styrene-butadiene-styrene block copolymer in Comparative Example 1. The remaining steps and component parameters of Comparative Example 1 are the same as those of Example 2.
[0114] Comparative Example 7 The main difference between Comparative Example 7 and Example 7 is that the fillers in Comparative Example 7 are all replaced with commercially available glass fibers. The remaining steps and component parameters of Comparative Example 7 are the same as those of Example 7.
[0115] Comparative Example 8 The main difference between Comparative Example 8 and Example 7 is that the tackifier and the crosslinking agent are omitted in Comparative Example 8. The remaining steps and component parameters of Comparative Example 8 are the same as those of Example 7.
[0116] Comparative Example 9 The main difference between Comparative Example 9 and Example 7 is that the emulsifier in Comparative Example 9 is replaced by commercially available octylphenol polyoxyethylene ether Triton x-100. The remaining steps and component parameters of Comparative Example 9 are the same as those of Example 7.
[0117] Comparative Example 10 The main difference between Comparative Example 10 and Example 7 is that the preparation method in Comparative Example 10 is modified as follows: A method for preparing surface emulsified asphalt comprises the following steps: S1. Stir corresponding amounts of stabilizer, water and emulsifier at 60° C. with a high-speed stirrer at 600 rpm for 5 min to obtain a first mixed solution, adjust the pH value to 3 with a pH adjuster, add an anti-stripping agent, an antioxidant, a tackifier, a plasticizer, a second filler and a cross-linking agent to the first mixed solution, and stir the mixture at 600 rpm with a high-speed stirrer for 10 minutes to obtain a basic soap solution; S2, heating the base asphalt to 150° C., adding a corresponding amount of asphalt modifier by mass, and stirring the mixture at 1200 rpm for 60 minutes using a high-speed mixer to obtain a surface emulsified asphalt; S3. Slowly add the modified matrix asphalt into the base soap solution and use a high-speed shear emulsifier to emulsify it at a shear speed of 5000 rpm and an emulsification time of 30 minutes to obtain a surface emulsified asphalt.
[0118] The component parameters of Comparative Example 10 are the same as those of Example 7.
[0119] The above embodiments and comparative examples were subjected to performance tests, wherein the test method for residual solid content was T0651, the test method for demulsification rate was T0658-1993, the test method for storage stability was T0655, the test method for ductility (10°, 5cm / min) was T0605, the test method for softening point (TR&B) was T0604, the test method for 60°C dynamic viscosity was T0620, the prepared emulsified asphalt was used to make test pieces according to the Marshall method, the test methods for viscosity (25°C) and toughness (25°C) were T0624, the test method for elastic recovery (25°) was T0662, the water permeability coefficient of the test piece with a molding thickness of 3 cm was tested, the time taken for the water level to drop from 1000 ml to 500 ml was tested by a water permeability coefficient measuring instrument, and the water permeability coefficient mL / min was obtained, and the wear rate was tested by a wet wheel abrasion test, and the test method was JTG E20-2011, T 0752-2011, the BPN value is determined by a pendulum friction coefficient tester.
[0120] The test data are shown in Table 3 and Table 4: Table 3: Performance test results of Examples 1-10
[0121] Table 4: Performance test results of comparative examples 1-10
[0122] Specifically, the water permeability coefficients of Examples 1-10 are 635, 627, 632, 674, 653, 721, 714, 728, 743, 735 mL / min, respectively, the BPN values of Examples 1-10 are 80.6, 81.2, 80.5, 81.1, 80.2, 82.3, 83.6, 82.8, 83.5, 82.1, respectively, and the wear rates of Examples 1-10 are 0.4, 0.4, 0.4, 0.4, 0.4, 0.3, 0.3, 0.3, 0.3, 0.3. As can be seen from Table 3, in Examples 1-10, the coordination between the raw materials can give full play to their respective roles and improve the comprehensive performance of the emulsified asphalt. The emulsified asphalt has excellent adhesion, waterproofness and durability, and is suitable for various road and bridge projects and waterproof projects. The preparation methods of Examples 1 to 10 can improve the mechanical strength of the bottom emulsified asphalt and the surface emulsified asphalt, and ensure the long-term stability and uniformity of the emulsified asphalt through pH adjustment and high-speed shear emulsification. The addition of tackifiers and plasticizers can improve the adhesion and flexibility of the emulsified asphalt, making it easier to construct. The bottom emulsified asphalt and the surface emulsified asphalt of Examples 1 to 10 have excellent film-forming properties, adhesion, and waterproof properties, which not only improve the interlayer bonding ability, but also enhance the durability of use. The application of super-sticky anti-skid seal in preventive maintenance construction can effectively improve the anti-skid performance and durability of the road surface, thereby extending the service life of the road and improving driving safety.
[0123] As shown in Table 4, compared with Example 2, and compared with Example 7, Comparative Example 1 and Comparative Example 6 use styrene-butadiene-styrene block copolymers as the asphalt modifiers. The water permeability coefficients of Comparative Example 1 and Comparative Example 6 are 723 mL and 796 / min, respectively. The BPN values of Comparative Example 1 and Comparative Example 6 are 77.6 and 78.8, respectively. The wear rates of Comparative Example 1 and Comparative Example 6 are 0.5 and 0.5, respectively. In Example 2 and Example 7, the combination of styrene-butadiene-styrene block copolymer and styrene-butadiene rubber can make the emulsified asphalt not easy to flow and deform at high temperatures, maintain good flexibility at low temperatures, and reduce the generation of cracks. The combination of styrene-butadiene-styrene block and ethylene-vinyl acetate copolymer can make the emulsified asphalt resist the erosion of aging factors such as ultraviolet rays and oxidation during long-term use, and maintain good bearing capacity under vehicle load. The combination of styrene-butadiene rubber and ethylene-vinyl acetate copolymer makes the emulsified asphalt perform well in bonding aggregates, and can also maintain good performance under complex environmental conditions. For example, in a humid environment, due to good bonding, the peeling of aggregates can be reduced, and under long-term sun and rain, its aging resistance can ensure the stability of the road surface. Example 2 and Example 7 are better in ductility, softening point, viscosity, toughness, elastic recovery, wear resistance, and skid resistance. Therefore, the mechanical properties, aging resistance, and temperature resistance of Comparative Example 1 are worse than those of Example 2, and the mechanical properties, aging resistance, and temperature resistance of Comparative Example 6 are worse than those of Example 7.
[0124] Comparative Example 2 Compared with Example 2, Comparative Example 2 uses commercially available silicon dioxide. The water permeability coefficient of Comparative Example 2 is 1023mL / min, the BPN value of Comparative Example 2 is 78.9, and the wear rate of Comparative Example 2 is 0.6. The filler of Example 2 can prepare an excellent bottom emulsified asphalt, and these fillers can form a multi-level filling network in the asphalt to enhance the mechanical properties and durability of the coating. At the same time, due to the synergistic effect between different fillers, the comprehensive properties of the coating can be further improved, such as improving the hardness, wear resistance, heat resistance, weather resistance and bonding strength of the coating. Therefore, the mechanical properties, aging resistance, water resistance, temperature resistance, wear resistance and skid resistance of Comparative Example 2 are worse than those of Example 2.
[0125] Compared with Example 7, Comparative Example 7 uses commercially available glass fiber. The water permeability coefficient of Comparative Example 2 is 1223 mL / min, the BPN value of Comparative Example 2 is 79.8, and the wear rate of Comparative Example 7 is 0.7. The filler of Example 7 can prepare a surface emulsified asphalt with excellent performance. The second filler can comprehensively improve the wear resistance, skid resistance, mechanical properties, stability and durability of the surface emulsified asphalt, thereby further improving the overall performance of the super-sticky anti-skid seal layer. Therefore, the mechanical properties, aging resistance, water resistance, temperature resistance, wear resistance, and skid resistance of Comparative Example 7 are worse than those of Example 7.
[0126] Comparative Example 3 is compared with Example 2, and Comparative Example 8 is compared with Example 7. Comparative Example 3 and Comparative Example 8 both omit the tackifier and cross-linking agent. The water permeability coefficients of Comparative Example 3 and Comparative Example 8 are 1123 and 1242 mL / min, respectively. The BPN values of Comparative Example 3 and Comparative Example 8 are 76.6 and 78.1, respectively. The wear rates of Comparative Example 3 and Comparative Example 8 are 0.4 and 0.3, respectively. The tackifiers of Example 2 and Example 7 use the high-viscosity modifier PT-HVA of drainage asphalt pavement of Guolu New Materials, which includes epoxy tackifying resin and thermoplastic elastomer, which can increase the absolute viscosity of asphalt and has the characteristics of high softening point, high elastic recovery, high viscosity toughness, high anti-aging, etc. As the water evaporates continuously, the asphalt particles in the emulsified asphalt begin to aggregate to form a continuous asphalt film. The terephthalate glycol and dimethoxymethane of Example 2 and Example 7 can play a synergistic role in the modified super-viscous emulsified asphalt. The three-dimensional network structure constructed by phenylene glycol provides a basic strength and stability framework for emulsified asphalt, while dimethoxymethane plays a role in curing promotion and chemical resistance. The combination of the two can significantly improve the strength, stability, aging resistance, water resistance and chemical corrosion resistance of emulsified asphalt. Therefore, the 60°C dynamic viscosity of Comparative Example 3 is lower than that of Example 2, and the storage stability, water resistance, mechanical properties, aging resistance, temperature resistance and skid resistance of Comparative Example 3 are all worse than those of Example 2. The 60°C dynamic viscosity of Comparative Example 8 is lower than that of Example 7, and the storage stability, water resistance, mechanical properties, aging resistance, temperature resistance and skid resistance of Comparative Example 8 are all worse than those of Example 7.
[0127] Comparative Example 4 is compared with Example 2, and Comparative Example 9 is compared with Example 7. The emulsifier used in both Comparative Example 4 and Comparative Example 9 is commercially available octylphenol polyoxyethylene ether Triton x-100. The water permeability coefficients of Comparative Example 4 and Comparative Example 9 are 683 and 811 mL / min, respectively. The BPN values of Comparative Example 4 and Comparative Example 9 are 77.6 and 78.2, respectively. The wear rates of Comparative Example 4 and Comparative Example 9 are 0.4 and 0.3, respectively. The fatty amine cationic emulsifiers of Example 2 and Example 7 have lipophilic groups and hydrophilic groups. The lipophilic groups can combine with asphalt, and the hydrophilic groups can interact with water. Through the mechanical force such as high-speed shearing, the asphalt is evenly dispersed in the water in the form of tiny particles, and a stable emulsion system is formed. The cationic emulsifier will be adsorbed on the surface of the asphalt particles in the emulsion, so that the asphalt particles have a positive charge. Since the same charges repel each other, this electrostatic repulsion can prevent the asphalt particles from aggregating with each other, thereby improving the stability of the emulsion and extending the storage time of the emulsified asphalt. In asphalt pavement construction, emulsifiers can significantly reduce the viscosity of asphalt, making it easier to spread and compact, thereby improving construction efficiency. Fatty amine cationic emulsifiers can enhance the adhesion of asphalt to substrates such as stone, and improve the durability and water damage resistance of the pavement. Triton x-100 is a nonionic surfactant. The foam of Triton x-100 is relatively more than that of cationic emulsifiers. The demulsification speed of asphalt emulsified by TritonX-100 is relatively slow. Under normal environmental conditions, it can keep the emulsified asphalt in an emulsion state for a long time, which provides more ample time for construction operations. Therefore, the demulsification speed, storage stability, mechanical properties, aging resistance, and temperature resistance of Comparative Example 4 are worse than those of Example 2. Therefore, the demulsification speed, storage stability, mechanical properties, aging resistance, and temperature resistance of Comparative Example 9 are worse than those of Example 7. Comparative Examples 4 and Comparative Examples 9 have long demulsification times, and their implementation of the spreading process will also affect the overall construction progress.
[0128] Compared with Example 2, and compared with Example 7, in Comparative Example 5, multiple materials of Comparative Example 5 and Comparative Example 10 are mixed simultaneously, and the water permeability coefficients of Comparative Example 5 and Comparative Example 10 are 943 and 1024 mL / min, respectively, and the BPN values of Comparative Example 5 and Comparative Example 10 are 75.3 and 77.2, respectively, and the wear rates of Comparative Example 5 and Comparative Example 10 are 0.4 and 0.3, respectively. The filler in Comparative Example 5 is easier to agglomerate during mixing than that in Example 2, and the thickener in Comparative Example 5 is not heated during mixing, resulting in incomplete mixing and dispersion of the thickener, and the overall viscosity cannot be completely improved, resulting in the storage stability, mechanical properties, aging resistance, water resistance, and temperature resistance of Comparative Example 5 being worse than those of Example 2. The filler in Comparative Example 10 is easier to agglomerate during mixing than that in Example 7, and the thickener in Comparative Example 5 is not heated during mixing, resulting in incomplete mixing and dispersion of the thickener and failure to completely improve the overall viscosity, resulting in the storage stability, mechanical properties, aging resistance, water resistance, and temperature resistance of Comparative Example 10 being worse than those in Example 7.
[0129] The crushed stone layer of the present invention is calculated by mass fraction to be 80 parts of basalt and 20 parts of diabase.
[0130] Table 5: Test results of crushed stone layer performance
[0131] Table 6: Grading index of crushed stone layer
[0132] Embodiment 11 The construction method of the super-adhesive anti-slip seal layer comprises the following steps: The road surface temperature is 28℃, S1, the original road markings are processed, and the original road surface is cleaned; S2. Loading and debugging related parameters; S3. Calculate the amount of bottom emulsified asphalt and crushed stone on site, and spread the bottom emulsified asphalt and crushed stone; Spread the bottom emulsified asphalt 0.9kg / m 2 , Crushed stone layer 4.0kg / m 2 , the crushed stone coverage rate is 110%, and the spreading speed is controlled at 50m / min; S4: Curing for 2 hours and rolling with an 8t rubber-wheel roller, rolling twice, rolling speed 15km / h, back and forth compaction overlapping rolling one wheel width, controlled at 20cm, residual material can be recovered 30 minutes after rolling, residual material recovery speed controlled at 3km / h, after residual material recovery, ensure that there is no loose gravel in the bottom layer; S5. Calculate the amount of surface emulsified asphalt on site and spread the surface emulsified asphalt; Spread the surface emulsified asphalt 0.4kg / m 2 ; S6: After spreading, cure for 2 hours; S7: Restore lane markings and open to traffic.
[0133] Example 12 The construction method of the super-adhesive anti-slip seal layer comprises the following steps: The road surface temperature is 25℃, S1, the original road markings are processed, and the original road surface is cleaned; S2. Loading and debugging related parameters; S3. Calculate the amount of bottom emulsified asphalt and gravel on site, and spread the bottom emulsified asphalt and gravel; Spread the bottom emulsified asphalt 1.2kg / m 2 , Crushed stone layer 5.5kg / m 2 , the crushed stone coverage rate is 100%, and the spreading speed is controlled at 100m / min; S4: Curing for 2 hours and rolling with an 8t rubber-wheel roller, rolling twice, rolling speed 20km / h, back and forth compaction overlapping rolling one wheel width, controlled at 20cm, residual material can be recovered 30 minutes after rolling, residual material recovery speed controlled at 6km / h, after residual material recovery, ensure that there is no loose gravel in the bottom layer; S5. Calculate the amount of surface emulsified asphalt on site and spread the surface emulsified asphalt; Spread the surface emulsified asphalt 0.6kg / m 2 ; S6: After spreading, cure for 2 hours; S7: Restore lane markings and open to traffic.
[0134] Example 13 The construction method of the super-adhesive anti-slip seal layer comprises the following steps: The road surface temperature is 20℃, S1, the original road markings are processed, and the original road surface is cleaned; S2. Loading and debugging related parameters; S3. Calculate the amount of bottom emulsified asphalt and crushed stone on site, and spread the bottom emulsified asphalt and crushed stone; Spread the bottom emulsified asphalt 0.95kg / m 2 , gravel layer 4.3kg / m 2 , the crushed stone coverage rate is 100%, and the spreading speed is controlled at 70m / min; S4: Curing for 3 hours and rolling with an 8t rubber-wheel roller, rolling twice, rolling speed 17km / h, back and forth compaction overlapping rolling one wheel width, controlled at 30cm, residual material can be recycled 30 minutes after rolling, residual material recycling speed controlled at 4km / h, after residual material recycling, ensure that there is no loose gravel in the bottom layer; S5. Calculate the amount of emulsified asphalt on the surface and spread it on the surface. Spread 0.45kg / m 2 ; S6: After spreading, cure for 3 hours; S7: Restore lane markings and open to traffic.
[0135] Embodiment 14 The construction method of the super-adhesive anti-slip seal layer comprises the following steps: The road surface temperature is 15℃, S1, the original road markings are processed, and the original road surface is cleaned; S2. Loading and debugging related parameters; S3. Calculate the amount of bottom emulsified asphalt and crushed stone on site, and spread the bottom emulsified asphalt and crushed stone; Spread the bottom emulsified asphalt 1.15kg / m 2 , Crushed stone layer 5.0kg / m 2 , the crushed stone coverage rate is 110%, and the spreading speed is controlled at 90m / min; S4: Curing for 4 hours and rolling with an 8t rubber-wheel roller, rolling twice, rolling speed of 18km / h, rolling back and forth for overlapping one wheel width, controlled at 30cm, and the remaining material can be recycled 30 minutes after the rolling is completed, and the recycling speed of the remaining material is controlled at 5km / h. After the remaining material is recycled, it should be ensured that there is no loose gravel in the bottom layer; S5. Calculate the amount of surface emulsified asphalt on site and spread the surface emulsified asphalt; Spread the surface emulsified asphalt 0.55kg / m 2 ; S6: After spreading, cure for 4 hours; S7: Restore lane markings and open to traffic.
[0136] Embodiment 15 The construction method of the super-adhesive anti-slip seal layer comprises the following steps: The road surface temperature is 10℃, S1, the original road markings are processed, and the original road surface is cleaned; S2. Loading and debugging related parameters; S3. Calculate the amount of bottom emulsified asphalt and crushed stone on site, and spread the bottom emulsified asphalt and crushed stone; Spread the bottom emulsified asphalt 0.98kg / m 2 , gravel layer 4.1kg / m 2 The crushed stone coverage rate is 110%, and the spreading speed is controlled at 90m / min; the heating system of the crushed stone sealing vehicle is turned on synchronously to heat the bottom emulsified asphalt to 50℃; S4: Curing for 4 hours and rolling with an 8t rubber-wheel roller, rolling twice, rolling speed of 18km / h, rolling back and forth for overlapping one wheel width, controlled at 30cm, and the remaining material can be recycled 30 minutes after the rolling is completed, and the recycling speed of the remaining material is controlled at 5km / h. After the remaining material is recycled, it should be ensured that there is no loose gravel in the bottom layer; S5. Calculate the amount of surface emulsified asphalt on site and spread the surface emulsified asphalt; Spread the surface emulsified asphalt 0.42kg / m2 ; The heating system of the chip seal vehicle is turned on synchronously to heat the emulsified asphalt of the facing layer to 50℃; S6: After spreading, cure for 4 hours; S7: Restore lane markings and open to traffic.
[0137] The above is a preferred embodiment of the present invention. Relevant personnel in this technical field may make several improvements and modifications without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A super-sticky anti-slip seal layer, characterized in that: It includes a base layer of emulsified asphalt, a crushed stone layer and a surface layer of emulsified asphalt. The base layer of emulsified asphalt is made of the following raw materials in parts by weight: 65-75 parts of base asphalt, 3-8 parts of asphalt modifier, 10-15 parts of a first filler, 3-5 parts of a tackifier, 2-5 parts of an emulsifier, 3-5 parts of a stabilizer, 3-5 parts of a cross-linking agent, 30-40 parts of water, and 5-8 parts of an auxiliary agent. The surface layer of emulsified asphalt is made of the following raw materials in parts by weight: 65-75 parts of base asphalt, 3-8 parts of an asphalt modifier, 15-20 parts of a second filler, 3-5 parts of a tackifier, 2-5 parts of an emulsifier, 3-5 parts of a stabilizer, 3-5 parts of a cross-linking agent, 30-40 parts of water, and 5-8 parts of an auxiliary agent.
2. The super-adhesive anti-slip seal layer according to claim 1, characterized in that: The base asphalt is one of No. 70 or No. 90 road petroleum asphalt, and the asphalt modifier includes at least two of styrene-butadiene-styrene block copolymer, styrene-butadiene rubber, and ethylene-vinyl acetate copolymer.
3. The super-adhesive anti-slip seal layer according to claim 1, characterized in that: The first filler includes at least three of modified silicon dioxide, nano calcium carbonate, polypropylene composite particles, modified montmorillonite, and modified carbon nanotubes.
4. The super-adhesive anti-slip seal layer according to claim 1, characterized in that: The second filler includes at least three of ultra-high molecular weight polyethylene, basalt particles, silicon carbide, glass fiber, and wollastonite.
5. The super-adhesive anti-slip seal layer according to claim 1, characterized in that: The tackifier comprises epoxy tackifier resin and thermoplastic elastomer, and the emulsifier is a fatty amine cationic emulsifier.
6. The super-adhesive anti-slip seal layer according to claim 1, characterized in that: The stabilizer includes one or both of polyvinyl alcohol solution and polyacrylamide solution, and the cross-linking agent includes terephthalate and dimethoxymethane.
7. The super-adhesive anti-slip seal layer according to claim 1, characterized in that: The gravel layer includes one or both of basalt and diabase.
8. The super-adhesive anti-slip seal layer according to claim 1, characterized in that: The auxiliary agent includes an anti-stripping agent, an antioxidant, a plasticizer, and a pH regulator. The anti-stripping agent is at least one of calcium stearate and zinc acetate, the antioxidant is β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, the plasticizer is alkyl sulfonate, and the pH regulator includes hydrochloric acid and sodium hydroxide.
9. A construction method for a super-adhesive anti-slip seal layer according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Process the original road markings and clean the original road surface; S2. Loading and debugging related parameters; S3. Calculate the amount of bottom emulsified asphalt and crushed stone on site, and spread the bottom emulsified asphalt and crushed stone; S4: Health and rolling; S5. Calculate the amount of surface emulsified asphalt on site and spread the surface emulsified asphalt; S6: Health preservation; S7: Restore lane markings and open to traffic.
10. The use of a super-adhesive anti-slip seal layer according to any one of claims 1 to 8, characterized in that: The super-adhesive anti-skid sealing layer is used in the preventive maintenance construction of the super-adhesive anti-skid sealing layer.
